Synthesis and studying of the mononuclear complex Cu (II) with 3,5-dimethyl-1H-pyrazole: UDC: 54-386+546.562+547.772 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The product of addition the cyanate ion to the 3,5-dimethyl-1H-pyrazole, the mononuclear complex of copper (II) has been synthesizedand characterized by a variety of spectral methods. X-ray single crystal analysis revealed that the compound has molecular structure. Inthis complex two anions of 3,5-dimethylpyrazolcarbaminate which was formed in the course of the synthesis, are coordinated to the Cu(II)in a bidentate mode via two nitrogen atoms generating square-planar coordination environment with trans-disposition of the ligands.
Keywords: -